Epimedin C Alleviates Glucocorticoid-Induced Suppression of Osteogenic Differentiation by Modulating PI3K/AKT/RUNX2 Signaling Pathway - Xu, Yongxiang; Chen, Shichun; Huang, Linxuan; Han, Weichao; Shao, Yingying; Chen, Minyi; Zhang, Yusheng; He, Ruirong; Xie, Baocheng (Frontiers in Pharmacology, 2022)
Abstract: Secondary osteoporosis is triggered mostly by glucocorticoid (GC) therapy. Dexamethasone (DEX) was reported to inhibit osteogenic differentiation in zebrafish larvae and MC3T3-E1 cells in prior research. In this research, we primarily examined the protective impacts of epimedin C on the osteogenic inhibition impact of MC3T3-E1 cells and zebrafish larvae mediated by DEX. The findings illustrated no apparent toxicity for MC3T3-E1 cells after administering epimedin C at increasing dosages from 1 μM to 60 μM and no remarkable proliferation in MC3T3-E1 cells treated using DEX. In MC3T3-E1 cells that had been treated using DEX, we discovered that epimedin C enhanced alkaline phosphatase activities and mineralization. Epimedin C could substantially enhance the protein expression of osterix (OSX), Runt-related transcription factor 2 (RUNX2), and alkaline phosphatase (ALPL) in MC3T3-E1 cells subjected to DEX treatment. Additionally, epimedin C stimulated PI3K and AKT signaling pathways in MC3T3-E1 cells that had been treated using DEX. Furthermore, in a zebrafish larvae model, epimedin C was shown to enhance bone mineralization in DEX-mediated bone impairment. We also found that epimedin C enhanced ALPL activity and mineralization in MC3T3-E1 cells treated using DEX, which may be reversed by PI3K inhibitor (LY294002). LY294002 can also reverse the protective impact of epimedin C on DEX-mediated bone impairment in zebrafish larval. These findings suggested that epimedin C alleviated the suppressive impact of DEX on the osteogenesis of zebrafish larval and MC3T3-E1 cells via triggering the PI3K and AKT signaling pathways. Epimedin C has significant potential in the development of innovative drugs for the treatment of glucocorticoid-mediated osteoporosis.